Student identification and grading system based on NFC and blockchain based on nfc and blockchain technology (COLOMBIAN JOURNAL OF ADVANCED TECHNOLOGIES, 2023)
The problem addressed in the paper deals with the precariousness of the traditional roll-call systems that some universities have. Research was done on the characteristics of NFCs and how they can be used for an academic staff identification system for universities. It was kept in mind to use blockchain to take advantage of the decentralized nature of that network to ensure the confidentiality of the users of the identification system. An architecture was developed to apply these two technologies in a single system that leverages the best of both centralized systems and decentralized networks. This allowed the development of a Dapp that allows the reading of NFC's, which will be the ID cards of the university assistants, to access their information, role and identification in the university.
Keywords: NFC; Blockchain; Dapps; Decentralization; Security; Access